FAKTOR-FAKTOR PENGARUH KINERJA EKSPOR BATIK PEKALONGAN (Studi pada industri batik di Pekalongan) - Istikomah Nugrahawati; Suryadi Poerbo; Khairul Saleh (Politeknik Negeri Semarang, 2015)
This research is aimed to know the influence of firm, relationships, marketing strategy, environment on export performance in the city of Pekalongan batik industry. The methods of data collection are interview and questionnair completion. The sample of this research were 30 respondents and analytical method used were the validity test, reliability test, multiple linear regression method, classical assumption test, t test, F test.The result of regression analysis indicates that firm, relationships, marketing strategy and environment have positive influence on export performance. Based on t test, indicated variable firm, relationships, marketing strategy have positive significant influence on export performance, whereas environment variable do not have positive significant on export performance.. Based on F test, independent variables simutaneuosly influence the work satisfaction significantly, with coefficient of determination (??) of 0,514. This means that 54,7% work statisfaction could be explained by firm, relationships, marketing strategy and environment.